Analysis of the Role of Family Support in Treatment Compliance of Pulmonary Tuberculosis Clients - Sugiyanto, Sugiyanto; Sigala, Aprianti (Baiman Bauntung Batuah Center, 2023)
Pulmonary tuberculosis is a deadly infectious disease caused by Mycobacterium tuberculosis. Pulmonary tuberculosis is very easily resistant to drugs, so treating it takes a long time. In the process of treatment, the role of the family is needed as the closest unit to the patient to supervise. This study aimed to determine the relationship between the part of family support and adherence to treatment of pulmonary tuberculosis clients. The research design used was analytic descriptive research with a cross-sectional study approach. The sample in this study was 30 people, who were taken using the total sampling technique—data analysis using Chi-square on SPSS. The results showed that the role of a good family was 53.3% and less was 46.7%. The frequency of client compliance is 80% and 20% non-compliant. The results of the statistical test showed that the p-value was smaller than the ? value, which meant that there was a relationship between the role of family support and adherence to treatment for pulmonary tuberculosis clients in the working area of ??the Wara Public Health Center, Palopo City, South Sulawesi Province, Indonesia. The long process of treating pulmonary TB will result in boredom and boredom in patients. Therefore, the family has an important role in monitoring and increasing the motivation of pulmonary TB patients to remain consistent in the treatment process. As the frontline in disease prevention and rehabilitation, health workers must always be active in providing health education to the community, especially to families of pulmonary TB sufferers, about the importance of family support in the patient's treatment process.